1990
DOI: 10.1002/hed.2880120605
|View full text |Cite
|
Sign up to set email alerts
|

Modified radical neck dissection in cancer of the mouth, pharynx, and larynx

Abstract: A retrospective analysis of 390 determinate radical neck dissections (RND) performed for cancers of the mouth, pharynx, and larynx was carried out. There were 75 patients (19%) who had a modified RND. These were separately analyzed and the outcome was compared to those who had a standard total RND. Our goal was to assess the effectiveness of modified RND in controlling disease in the neck, and to identify its impact on survival and quality of life. Overall neck recurrence rate in the entire modified RND group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Functional neck dissection was initially introduced into clinical practice by Bocca, and in recent years, this has been advocated for different types of primary carcinomas (Khafif et al, 1990). Indeed, functional neck dissection resulted in regional control rates similar to those acheived by RND, not only in carcinoma of the larynx but also for cancers at other sites especially when patients were carefully selected (Bocca et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Functional neck dissection was initially introduced into clinical practice by Bocca, and in recent years, this has been advocated for different types of primary carcinomas (Khafif et al, 1990). Indeed, functional neck dissection resulted in regional control rates similar to those acheived by RND, not only in carcinoma of the larynx but also for cancers at other sites especially when patients were carefully selected (Bocca et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…5,19,20 In patients with clinical N1 disease and selected N2 disease, am odified radical neck dissection may be done for better cosmetic and functional results. [19][20][21] Preservation of the spinal accessory nerve, internal jugular vein (IJV) and sternocleidomastoid muscle is done in the form of am odified radial neck dissection (MRND ; Table 3). RND, however,i ss till appropriate for patients with massive lymphadenopathy (N3 disease), multiple positive nodes involving the spinal accessory nerve and/or the IJV,r esidual or recurrent neck disease after radiotherapy and gross extranodal spread.…”
Section: Treatment Of Neckmentioning
confidence: 99%
“…There was a 61% actuarial survival rate and 86% neck control rate at 5 years, but the authors were unable to demonstrate any statistical difference between the two dissection groups. In a similar study, Khafif et al 29 examined 118 patients with N2 to N3 disease and found that the 3-year actual survival and neck control rates were 56% and 64%, respectively.…”
Section: Discussionmentioning
confidence: 94%